ANALISIS PERBANDINGAN RENCANA ANGGARAN BIAYA PADA PROYEK DENGAN ANGGARAN BIAYA BERDASARKAN SNI 2023: (Studi Kasus : Pekerjaan Pembangunan Gedung PMI Boyolali) - Nursetyo, Gatot; Yuono, Teguh; Amhudo, Rasyiid Lathiif; Mufidati, Rossa Aruma (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2025)
The Cost Budget Plan (RAB) is an important step in a project because it is a reference for making an agreement on the payment method and calculation framework that will be announced as well as the estimated costs required. This study aims to compare and obtain more efficient estimation results according to Contractor based on the SNI method. Data collection method used in this final study is by using Secondary data, namely by collecting information on labor and material prices from the Contractor, as well as from the SNI Guidelines. Based on the results of this study, the amount of the RAB for the PMI Boyolali Building Construction Project if based on the price of the implementing contractor for the construction is Rp. 4,431,436,659. Furthermore, RAB amount for the PMI Boyolali Building Project Construction if calculated using the Boyolali Regency unit price analysis in 2023 is Rp. 4,613,231,520. And the work that has a large difference between RAB for Implementation Costs in the PMI Boyolali Building Construction Work and the RAB based on the Boyolali Regency AHSP 2023 is the highest deviation compared to other work descriptions, namely having a total difference of -Rp. 94,935,992.04, namely in the job description: concrete work (structural), concrete work (non-structural), wall work, plastering work, ceramic and floor work, and sanitation work